Protein microarray allergen profiling in bronchoalveolar lavage fluid and serum of horses with asthma. (8th December 2022) - Wyler, Michelle; Sage, Sophie Elena; Marti, Eliane; White, Samuel; Gerber, Vinzenz
Abstract: Background: The diagnostic value of allergen‐specific immunoglobulin E (IgE) in horses with asthma is uncertain. A recently developed protein microarray detected abnormally high latex‐specific IgE concentrations in the serum of horses with severe asthma. Objectives: The main objective was to characterize the IgE profiles of asthmatic horses in Switzerland using a protein microarray platform in serum and bronchoalveolar lavage fluid (BALF). The secondary objective was to determine whether serological and BALF allergen‐specific IgE concentrations correlated. Animals: Forty‐four asthmatic and 39 control horses ≥5 years of age. Methods: This prospective cross‐sectional study investigated the sensitization profiles of horses with asthma compared with environmentally matched healthy controls. Both serum and BALF were analyzed using the protein microarray. Partial least square‐discriminant analysis (PLS‐DA) was used to identify and rank the importance of the allergens for class detection (ie, asthma vs control), with a variable influence on the projection (VIP) >1 considered significant. Results: The allergens that best discriminated (VIP >1) asthmatic horses from controls were proteins derived from fungi ( Aspergillus fumigatus ), insects ( Culicoides spp.), and latex ( Hevea brasiliensis ). The serological model predictive ability was markedly inferior (area under the curve [AUC] 0.585, 95% confidence interval [CI]: 0.454‐0.747) to that of the BALF (AUC 0.751, 95% CI: 0.582‐0.866). The two models shared nine allergens, of which eight showed significant weak to moderate correlations. Conclusion and Clinical Importance: The concentrations of several allergen‐specific IgE were higher in asthmatic horses. The protein microarray performed better on BALF than serum for detection of asthma. Serological IgE concentrations do not closely correlate with BALF concentrations and should be interpreted with caution.